Pengaruh Beberapa Jenis Fermentor terhadap Kandungan Protein Kasar, Serat Kasar, dan Lemak Kasar Jerami Jagung - Malaya Khaerul Hardi, Lalu; Yanuarianto, Oscar; Al Gifari, Zaid (Master’s Program in Biology, Faculty of Mathematics and Natural Sciences, University of Mataram, 2025)
This study aimed to evaluate the effect of different fermentors on the crude protein (CP), crude fat (CF), and crude fiber (CFb) content of fermented corn straw as an alternative feed for ruminants. The experiment was conducted at the Laboratory of Animal Nutrition and Feed Science, Faculty of Animal Husbandry, University of Mataram, using a Completely Randomized Design (CRD) with four treatments and three replications: P0 (untreated/control), P1 (fermented with 1.5% EM4), P2 (fermented with 1.5% MA-11), and P3 (fermented with 1.5% Starbio). Fermentation lasted 21 days, followed by proximate analysis. The results showed that the type of fermentor significantly affected (P < 0.05) the nutrient composition of corn straw, with an increase in CP and CF, and a decrease in CFb. EM4 yielded the highest CP content (4.73%), while Starbio produced the highest CF content (1.42%) and the lowest CFb content (31.79%). In conclusion, fermentation using Starbio was the most effective in improving the nutritional quality of corn straw, particularly through enhanced CP and CF levels and reduced CFb content